Immune profile of primary and recurrent epithelial ovarian cancer cases indicates immune suppression, a major cause of progression and relapse of ovarian cancer - Pavan Kumar; Samruddhi Ranmale; Sanket Mehta; Hemant Tongaonkar; Vainav Patel; Amit Kumar Singh; Jayanti Mania-Pramanik (BMC, 2023)
Abstract Background Ovarian cancer is the third most prevalent cancer in Indian women. Relative frequency of High grade serous epithelial ovarian cancer (HGSOC) and its associated deaths are highest in India which suggests the importance of understanding their immune profiles for better treatment modality. Hence, the present study investigated the NK cell receptor expression, their cognate ligands, serum cytokines, and soluble ligands in primary and recurrent HGSOC patients. We have used multicolor flow cytometry for immunophenotyping of tumor infiltrated and circulatory lymphocytes. Procartaplex, and ELISA were used to measure soluble ligands and cytokines of HGSOC patients. Results Among the enrolled 51 EOC patients, 33 were primary high grade serous epithelial ovarian cancer (pEOC) and 18 were recurrent epithelial ovarian cancer (rEOC) patients. Blood samples from 46 age matched healthy controls (HC) were used for comparative analysis. Results revealed, frequency of circulatory CD56Bright NK, CD56Dim NK, NKT-like, and T cells was reduced with activating receptors while alterations in immune subsets with inhibitory receptors were observed in both groups. Study also highlights differential immune profile of primary and recurrent ovarian cancer patients. We have found increased soluble MICA which might have acted as "decoy" molecule and could be a reason of decrease in NKG2D positive subsets in both groups of patients. Furthermore, elevated level of serum cytokines IL-2, IL-5, IL-6, IL-10, and TNF-α in ovarian cancer patients, might be associated with ovarian cancer progression. Profiling of tumor infiltrated immune cells revealed the reduced level of DNAM-1 positive NK and T cells in both groups than their circulatory counterpart, which might have led to decrease in NK cell's ability of synapse formation. Conclusions The study brings out differential receptor expression profile on CD56BrightNK, CD56DimNK, NKT-like, and T cells, cytokines levels and soluble ligands which may be exploited to develop alternate therapeutic approaches for HGSOC patients. Further, few differences in the circulatory immune profiles between pEOC and rEOC cases, indicates the immune signature of pEOC undergoes some changes in circulation that might facilitated the disease relapse. They also maintains some common immune signatures such as reduced expression of NKG2D, high level of MICA as well as IL-6, IL10 and TNF-α, which indicates irreversible immune suppression of ovarian cancer patients. It is also emphasized that a restoration of cytokines level, NKG2D and DNAM-1on tumor infiltrated immune cells may be targeted to develop specific therapeutic approaches for high-grade serous epithelial ovarian cancer.